1991
DOI: 10.1016/s0022-5347(17)38030-8
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Stimulation of Phosphoinositide Hydrolysis in the Human Isolated Urinary Bladder

Abstract: The stimulatory action of carbachol and acetylcholine (ACh) on phosphoinositide turnover, as well as their contractile effects, were investigated in human isolated detrusor muscle. Carbachol, and ACh in combination with 10(-7) M physostigmine, induced increases in phosphoinositide turnover. However, at all the concentrations tested, carbachol was more effective than ACh (plus physostigmine), and at the highest concentration used (10(-4) M), the difference was significant (p less than 0.05). Also in a Ca(2+)-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 13 publications
2
39
0
Order By: Relevance
“…4) and to cause contraction through phosphoinositide hydrolysis (Andersson et al, 1991b;Harriss et al, 1995). In cat detrusor muscle, contraction induced by acetylcholine was found to be mediated via M 3 receptor-dependent activation of G q/11 and phospholipase C-␤ 1 and inositol tris phosphate (IP 3 )-dependent Ca 2ϩ release .…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…4) and to cause contraction through phosphoinositide hydrolysis (Andersson et al, 1991b;Harriss et al, 1995). In cat detrusor muscle, contraction induced by acetylcholine was found to be mediated via M 3 receptor-dependent activation of G q/11 and phospholipase C-␤ 1 and inositol tris phosphate (IP 3 )-dependent Ca 2ϩ release .…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…41 Stimulation of M 3 receptors has previously been considered to cause contraction through phosphoinositide hydrolysis. 42,43 However, Jezior et al 44 suggested that muscarinic receptor activation of detrusor muscle includes both non-selective cation channels and activation of Rho-kinase. Supporting a role of Rho-kinase in the regulation of rat detrusor contraction and tone, Wibberley et al 45 found that in the rat, Rho-kinase inhibitors (Y27632, HA-1077) inhibited contractions evoked by carbachol without affecting the contraction response to KCl.…”
Section: Rho-kinase and Bladder Contractionmentioning
confidence: 99%
“…These results show that levcromakalim relaxes detrusor smooth muscle, possibly by hyperpolarizing the cell membrane by opening K+ (Iacovou et al 1990;Andersson et al 1991). A second intracellular system of Ca2+ mobilization involving Ca2+_ induced Ca2+ release (CICR) occurs in many smooth muscle cells.…”
Section: Germanymentioning
confidence: 89%
“…Cultured bladder smooth muscle cells have been used to demonstrate agonist-induced Ca2+ mobilization directly (Chambers & Gillespie, 1994) and the ability of agonists to stimulate phosphoinositide turnover in human bladder has been reported (Andersson et al 1991 Strips of guinea-pig aorta were suspended in an organ bath and perfused (IP3 ml min') at 37°C with a physiological salt solution (PSS) containing (mM): 112 NaCl, 5 KCl, 1 MgCl2, 18 CaCl2, 5 Hepes, 0 5 KH2PO4, 0 5 NaH2PO4, 15 NaHCO3, 10 glucose and 0-02 Phenol Red, (pH 7 4, 95% 02 and 5% C02). Tension was measured isometrically, and muscle strips precontracted either with phenylephrine (PE; 3-6 /uM) or by raising extracellular K+ concentration by an equimolar replacement of NaCl for KCI.…”
Section: Germanymentioning
confidence: 99%